2018
DOI: 10.1002/ps.5118
|View full text |Cite
|
Sign up to set email alerts
|

Methionine as a safe and effective novel biorational mosquito larvicide

Abstract: EPA regulations currently exempt methionine in pesticide formulations applied to agricultural crops. This study demonstrates that methionine is a highly effective mosquito larvicide that can provide a beneficial new biorational, environmentally sustainable tool to control pestiferous mosquitoes. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
(37 reference statements)
0
12
0
1
Order By: Relevance
“…albopictus and Cx. tarsalis [ 122 ], suggesting that similar processes could occur in mosquitoes. Another study in Drosophila showed that the production of lithocholic acid by the adult gut microbiota elongated host survival through upregulation of genes involved in glucose homeostasis [ 123 ], offering a potential target in the host to shorten lifespan.…”
Section: Influence Of Microbiota On Probability Of Vector Daily Survival (P)mentioning
confidence: 99%
“…albopictus and Cx. tarsalis [ 122 ], suggesting that similar processes could occur in mosquitoes. Another study in Drosophila showed that the production of lithocholic acid by the adult gut microbiota elongated host survival through upregulation of genes involved in glucose homeostasis [ 123 ], offering a potential target in the host to shorten lifespan.…”
Section: Influence Of Microbiota On Probability Of Vector Daily Survival (P)mentioning
confidence: 99%
“…Mosquitoes are global disease vectors that transmit diseases such as malaria, Chikungunya and dengue fever. To limit the spread of these disease vector mosquitoes, researchers have identified larval mosquito control as a highly effective public health tool (Weeks et al, 2019). In particular, naturally occurring larvicides such as methionine and Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, naturally occurring larvicides such as methionine and Bacillus sp. bacteria have recently increased in popularity as an environmentally safe alternative to synthetic insecticides such as DDT (Weeks et al, 2019;Regis et al, 2000). These larvicides must be ingested by larvae to be effective, and many factors affect larval feeding rate, including foraging strategy, chemosensory preference and competition with conspecifics or individuals from other species (Hartman, 2016;Ramoska and Hopkins, 1981;Merritt et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…albopictus and Cx. tarsalis [109], suggesting that similar processes could occur in mosquitoes. Another study in Drosophila showed that the production of lithocholic acid by the gut microbiota elongated host survival through upregulation of genes involved in glucose homeostasis [110], offering a potential target in the host to shorten lifespan.…”
Section: Adult Nutrition and Fitnessmentioning
confidence: 84%